The psychology of school bullying - Smith, Peter K. 1943- (The psychology of everything, 2019)
"The Psychology of Bullying provides a highly accessible overview about the nature of bullying, what is known about it, its possible effects, and what can be done about it. It focuses on bullying at school with special attention given to the development of cyberbullying, and a final chapter looks at bullying in other contexts. Illustrated with examples and case studies, it examines who bullies and who gets bullied, what is known about effective coping strategies, and what friends, peers and the school can do to help. It will be essential reading for students, teachers and parents looking for psychological insights into what bullying is" ...